2010
DOI: 10.1007/s10620-010-1149-x
|View full text |Cite
|
Sign up to set email alerts
|

Anti-thymocyte Globulin for the Treatment of Acute Cellular Rejection Following Liver Transplantation

Abstract: ATG effectively reversed severe and SSR; HCV recurrence and infections remain significant complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 35 publications
3
37
1
1
Order By: Relevance
“…Following the promising results from renal transplantation, the polyclonal antibody, ATG was used for the treatment of SRR in most LT centers. The results have been promising with most cases of SRR responding to ATG [27,28] . For treatment of rejection, ATG is usually started with a dose of 1.5 mg/kg per day intravenously.…”
Section: Monitoring Of the Immune Statusmentioning
confidence: 99%
See 2 more Smart Citations
“…Following the promising results from renal transplantation, the polyclonal antibody, ATG was used for the treatment of SRR in most LT centers. The results have been promising with most cases of SRR responding to ATG [27,28] . For treatment of rejection, ATG is usually started with a dose of 1.5 mg/kg per day intravenously.…”
Section: Monitoring Of the Immune Statusmentioning
confidence: 99%
“…Variable between centers, a single dose of 30 mg may be used in operating room ATG (Thymoglobulin ® , ATGAM ® ) [27][28][29][30] T cell depleting polyclonal antibody Induction of immunosuppression, treatment of steroid resistant rejection Variable between centers, For induction 1.5 mg/ kg per day iv for 3 d and for treatment of rejection 1.5 mg/kg per day iv for 5-7 d of thymoglobulin may be used. For ATGAM a higher dose of 15 mg/kg per day is usually used 2 Daclizumab (Zenapax ® ) [23,115] IL-2Ra, monoclonal antibody…”
Section: Induction Of Immunosuppressionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5] However, it has also been shown that the use of rabbit antithymocyte globulin (rATG) as induction therapy or therapy of steroid-resistant ACR is associated with increased risk of aggressive HCV recurrence. [6][7][8] Since 2000, our standard antibody induction protocol has included an interleukin 2 receptor (IL-2R) antibody. In the face of the increasing Model for EndStage Liver Disease (MELD) scores of our recipient population and the use of more expanded criteria deceased donors, in 2005, rATG was introduced as an alternative agent as a way to spare the kidney, with a later introduction of calcineurin drugs and minimized immunosuppressive load in the short and long term.…”
Section: Introductionmentioning
confidence: 99%
“…1 g/gün, 3 gün boyunca) ve/veya antilemfosit ajanlar (ATG-ALG) kullanılır. Akut rejeksiyon nadiren retransplantasyon gerektirebilir (58,(145)(146)(147)(148).…”
Section: Rejeksiyonunclassified